How the body works - Parker, Steve, 1952-; Reader's Digest Association (Pleasantville, N.Y. : Reader's Digest Association, 1994)
Basic facts about the human body. Includes experiments and projects with step-by-step instructions and photographs.
Includes index.
Subtitle on cover: 100 ways parents and kids can share the miracle of the human body.
Book Links (A.L.A.).
School Library Journal.
School Library Media Quarterly (A.A.A.L.).
Book Links (A.L.A.), May 1996.
Keywords: Human physiology -- Juvenile literature; Human physiology -- Experiments -- Juvenile literature; Physiology, Experimental -- Popular works -- Juvenile literature; Human physiology; Human physiology -- Experiments; Physiology; Physiology -- Experiments